Effect of Seed Pretreatments on Sunflower Seedling Tolerance in Soils Contaminated with Lead under Greenhouse Conditions - نجمه افتخار; S. Fallah; علی عباسی سورکی; حبیب خداوردی لو (علوم و فناوری بذر ایران, 2019)
Poor seedling establishment and total plant biomass reduction in contaminated soils, decrease the efficiency of phytoremediation techniques. In this study, the effects of different types of seed pretreatments (such as salicylic acid, and potassium nitrate) and three concentrations of lead (0, 200, 400 and 600 mg lead/kg soil) on sunflower seedling growth under greenhouse conditions were evaluated. These factorial experiment was conducted in completely randomized design with three replications in research greenhouse of Shahrekord University, in 2015. In general, the studied traits significantly decreased with increasing concentrations of lead. In most toxic concentrations of lead, Potassium nitrate and salicylic acid prevented the decreasing of dry weight of root compared to control up to 42%. Potassium nitrate prevented the decreasing of dry weight of leaf and chlorophyll a (with 24% and 60%, respectively), Salicylic acid prevented the decreasing of chlorophyll b (55%) compared to control. Shoot dry weight didn’t affect by seed priming treatments. Increasing in concentrations of lead elevated carotenoids, proline content and electrolyte leakage. Salicylic acid treatment reduced of electrolyte leakage (by 21%). Potassium nitrate prevents the increasing of carotenoids (by 24%), however increased proline content from 104 to 111 µm/g. Generally it could be concluded that salicylic acid and potassium nitrate increase seedling tolerance to lead toxicity through reducing carotenoids content, electrolyte leakage and increasing proline content. This technique can be used to increase the efficiency of phytoremediation of soils contaminated with lead.